Narratives of Crisis: Korean War Narratives and the Subject Formation of South Korea - Kang, Hye Yun (Global studies quarterly, 2025)
Abstract This article aims to show subject formation through narratives during the time of crisis with an example of Korean War narratives. Korean War narratives pose two important questions in understanding the relationship between the narrative and subject formation. First, how do subnarratives work in the forming of the subject? This question asks how a hegemonic narrative appears during crisis. The second question asks how the dynamic of hegemonic and subnarratives works with power relations in international politics. Given that the Korean War cannot be conceptualized without the Cold War context, power relations between the United States and South Korea intervened in the dynamic of hegemonic and subnarratives of the Korean War. Ontological security studies and the narrative approach in International Relations provide partial answers to these questions. On the one hand, ontological security studies does not provide enough understanding of local agencies empowered by fragmented war narratives. On the other hand, the narrative approach tends to focus on local narratives that counter the hegemonic narrative. Instead, I suggest looking at how local agencies are empowered through subnarratives and coopted by hegemonic narratives. This approach shows a different picture in which securitization narratives can become hegemonic because of, not in spite of, fragmented and incoherent subnarratives at the local level. This paper first focuses on how IR literature on narrative accommodates the question of narrative and subject formation during crisis. Second, it discusses fragmented and incongruent Korean war narratives and lastly, how these narratives are interwoven with local and central mobilizations.